Advances in unit operations and materials for the CuCl cycle of hydrogen production. (15th June 2017) - Naterer, G.F.; Suppiah, S.; Rosen, M.A.; Gabriel, K.; Dincer, I.; Jianu, O.A.; Wang, Z.; Easton, E.B.; Ikeda, B.M.; Rizvi, G.; Pioro, I.; Pope, K.; et al.
Abstract: This paper presents recent advances by an international team of five countries – Canada, U.S., China, Slovenia and Romania – on the development and scale-up of the copper–chlorine (CuCl) cycle for thermochemical hydrogen production using nuclear or solar energy. Electrochemical cell analysis and membrane characterization for the CuCl/HCl electrolysis process are presented. Constituent solubility in the ternary CuCl/HCl/H2 O system and XRD measurements are reported in regards to the CuCl2 crystallization process. Materials corrosion in high temperature copper chloride salts and performance of coatings of reactor surface alloys are examined. Finally, system integration is examined, with respect to scale-up of unit operations, cascaded heat pumps for heat upgrading, and linkage of heat exchangers with solar and nuclear plants. Highlights: Recent advances by an international team on the Cu–Cl cycle of hydrogen production Analysis and membrane characterization for the CuCl/HCl electrolysis process Constituent solubility in the ternary CuCl/HCl/H2O system for CuCl2 crystallization Materials corrosion and coatings in high temperature copper chloride salts Cascaded heat pumps for heat upgrading and linkage with solar and nuclear plants